Buckling analysis of tower shells under patch loading for self‐erecting wind energy plants. Issue 2 (1st September 2021) - Nikesch, Philip; Pak, Daniel; Korte, Sebastian
Abstract: To achieve a higher performance level and lower erection costs for wind turbines in the future, a concept for the automatic erection of a wind turbine with a hybrid tower was investigated in the FOSTA research project P1392. The tubular steel tower is lifted through the lattice tower using a strand lifting system and stabilized during this lifting process with the help of hydraulic cylinders arranged in two levels in the transition piece. This stabilization results in a transverse pressure acting on the tower shell, which does not occur in the load cases during operation, but only in the construction state. In this paper, the transverse forces (patch load) acting on the tower are investigated, whereby different system states are considered.